2003
DOI: 10.1002/ejoc.200300152
|View full text |Cite
|
Sign up to set email alerts
|

C‐Glycosidations of a 2‐Ketohexosyl Bromide with Electrophilic, Radical, and Nucleophilic Anomeric Carbons

Abstract: The susceptibility of acylated 2‐ketohexosyl halides to C‐homologation is demonstrated with the easily accessible tri‐O‐benzoyl‐α‐D‐arabino‐hexos‐ulosyl bromide 1 as the model compound. C‐Glycosidation with an electrophilic anomeric carbon requires prior carbonyl protection, to avoid carbonyl addition by the C‐nucleophile, for example, as the cyanohydrin. Silver triflate‐promoted reaction with the silylenol ether of acetophenone then efficiently yields the β‐phenacyl product. With thermal (AIBN) or photochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…136 The Reformatsky-type reaction of 2ketohexosyl bromide 87 with diacetonegalactose-6-aldehyde 88 in the presence of copper-activated zinc followed by βelimination of benzoate using NaHCO 3 gave the corresponding α-C-glycoside 89 in 73% yield. 137…”
Section: C-glycosylation With Glycosyl Halides Through Glycosyl Anion...mentioning
confidence: 99%
See 1 more Smart Citation
“…136 The Reformatsky-type reaction of 2ketohexosyl bromide 87 with diacetonegalactose-6-aldehyde 88 in the presence of copper-activated zinc followed by βelimination of benzoate using NaHCO 3 gave the corresponding α-C-glycoside 89 in 73% yield. 137…”
Section: C-glycosylation With Glycosyl Halides Through Glycosyl Anion...mentioning
confidence: 99%
“… Reductive samariation of the in situ generated glycosyl iodide 84 with SmI 2 led to an organosamarium­(III) species ( B ) that reacted with aldehyde 85 to give β- C -disaccharide 86 in 66% yield. , It was reported that the 2-deoxyglycosyl phosphonium salt prepared from glycosyl halide was subjected to benzaldehyde through Wittig olefination to afford exo -glycal in moderate yield . The Reformatsky-type reaction of 2-ketohexosyl bromide 87 with diacetonegalactose-6-aldehyde 88 in the presence of copper-activated zinc followed by β-elimination of benzoate using NaHCO 3 gave the corresponding α- C -glycoside 89 in 73% yield …”
Section: C-glycosylation With Glycosyl Halidesmentioning
confidence: 99%
“…The reaction may be effected even with electrophilic glycosyl radicals; α-d-arabino-hexopyranosyl-2-ulose bromide 6 reacts with methyl 2-(tributylstannylmethyl)acrylate albeit in moderate yield. 28 A study of the conformation-anomeric effect-stereoselectivity relationship in the anomeric radical reaction of pentopyranoses has been reported. Selectivity was increased by conformational restriction of the pentopyranose ring in 4 C 1 -chair 7 and completely inverted by flipping the conformation from the 4 C 1 -into the 1 C 4 -chair 8, because of the kinetic anomeric effect.…”
Section: Synthesis Of C-glycosidesmentioning
confidence: 99%
“…Anomeric cyanation of an acylated glycosyl halide has undoubtedly been the most practical C -extension method in terms of simplicity of reagents, workup procedures, and yields . However, exposure of ulosyl bromide 15 to Helferich cyanation conditions (mercuric cyanide in nitromethane for 1−2 d, rt) resulted in complex product mixtures; by contrast, reaction with trimethylsilyl cyanide/BF 3 ·OEt 2 was instantaneous, yet the anomeric bromine was not replaced by cyanide, but the cyanohydrin 77 , isolable in 87% yield, was formed quantitatively (TLC). , (Scheme ). Thus, of the two electrophilic carbons that may be attacked by cyanidedisplacement of bromine at C-1 or carbonyl addition at C-2the latter is strongly preferred, obviously due to the electron-withdrawing effect of the 2-carbonyl that diminishes the polarity of the C−Br bond.…”
Section: Ulosyl Donor Approach To β-D-man and β-L-rha Linkagesmentioning
confidence: 99%